The phospho-c-JUN (Ser63) content in mucosa cells under experimental development of gastric cancer - Tymoshenko, M.O.; Kravchenko, O.O.; Sokur, O.V.; Ostapchenko, L.I. (Experimental Oncology, 2014)
Aim: The aim of the study was to determine the phosphorylated c-Jun content and reduced and oxidized glutathione (GSH/GSSG) ratio in gastric mucosa cells during the process of gastric cancer development in rats. Materials and Methods: Gastric carcinogenesis was initiated in 80 white male rats by 10-week replacement of drinking water with 0.01% solution of N-methyl-N´-nitro-N-nitrosoguanidine, at the same time they were redefined on diet containing 5% NaCl. Then the animals were fed with standard vivarium diet till the end of 24th week. The gastric mucosa cells were examined at the end of 4th, 6th, 8th, 10th, 12th, 18th, and 24th weeks. Sandwich ELISA method was used to determine the content of phospho-c-Jun. The contents of GSH and GSSG were analyzed by spectrofluorymetric method with the use of orthophthalic aldehyde. Results: At the end of 6th, 8th, 10th weeks of MNNG and NaCl treatment the gastric mucosa cells were characterized by 4-, 6.3-, 1.9-fold higher content of phospho-c-Jun compared to the control, respectively, and 12, 18 and 24 weeks there was registered a stable increase of phospho-c-Jun content on the average at 3.6-fold compared to control values. Starting from 6th week of gastric cancer development an average decrease of GSH/GSSG was 3.4-fold compared with the control. Conclusion: During gastric carcinogenesis there was registered the decrease of GSH/GSSG ratio and increased level of phosphorylated c-Jun what points on MAP-kinase cascade activation in prooxidant conditions. Key Words: c-Jun, reduce glutathione (GSH), oxidized glutathione (GSSG), gastric cancer.